2007
DOI: 10.1103/physrevlett.98.057801
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Two Colloidal Crystals at the Nematic-Liquid-Crystal–Air Interface

Abstract: Glycerol droplets at a nematic-liquid-crystal-air interface form two different lattices--hexagonal and dense quasihexagonal--which are separated by the energy barrier and can coexist. Director distortions around each droplet form an elastic dipole. The first order transition between the two lattices is driven by a reduction of the dipole-dipole repulsion through reorientation of these dipoles. The elastic-capillary attraction is essential for the both lattices. The effect has a many-body origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 20 publications
(21 reference statements)
0
68
0
Order By: Relevance
“…Past studies of the interactions of microdroplets confined at the interface of a LC have also found evidence of attractive interdroplet interactions (4)(5)(6)(7)(19)(20)(21)(22)(23). The attractive forces were initially attributed to a many-bodied "elastic-capillary" interaction between microdroplets (5,7,19,20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Past studies of the interactions of microdroplets confined at the interface of a LC have also found evidence of attractive interdroplet interactions (4)(5)(6)(7)(19)(20)(21)(22)(23). The attractive forces were initially attributed to a many-bodied "elastic-capillary" interaction between microdroplets (5,7,19,20).…”
Section: Resultsmentioning
confidence: 99%
“…When one of the isotropic liquids is replaced by a LC, it has recently become evident that additional mechanisms of interparticle interactions are realized. For example, glycerol microdroplets formed by condensation at a nematic LC-air interface have been reported to spontaneously self-assemble into two-dimensional assemblies with hexagonal symmetry (5)(6)(7)(8). In this paper, we report on the reversible ordering of solid microparticles, with chemically functionalized surfaces, at LC-aqueous interfaces.…”
Section: Colloidal Interactions | Interfacial Assemblies | Liquid Crymentioning
confidence: 99%
“…A rough estimate of the order of magnitude of the elastic energy associated with the director distortions around a strongly anchored micron-size particle placed in an otherwise uniform nematic cell, is 56 . Forces of the same nature are also responsible for attraction of colloidal particles to (particle-free) distortions and defects in the director field in nematics 47,57,58 , smectics [59][60][61] and blue phases 62 , for trapping and ordering of particles at the LC surfaces [63][64][65][66] , and even for symmetry-breaking that enables transport phenomena such as nonlinear electrophoresis in LCs 45,67 . As discussed in the next…”
Section: Surface Anchoring and Two Types Of Liquid Crystal Colloidsmentioning
confidence: 99%
“…Cell thickness d, m As follows from the consideration above, location of a particle in a LC is dictated not only by gravity and Brownian motion, as in an isotropic fluid, but also by the director field, its gradients, balance of elastic and surface anchoring forces, as in Fig.7, by geometry and properties of bounding walls and interfaces, Fig.4,5 63,64 , by presence of other particles 33 , etc. Spectacular effects of linking colloidal particles into clusters by disclination lines have been demonstrated by Ljubljana group 49,54 .…”
Section: Static Distortionsmentioning
confidence: 99%
“…13,14 Subsequently, it has also been observed that the glycerol droplets form the different lattices-hexagonal and dense quasihexagonal which can coexist and are separated by the energy barrier. 15 Yamamato et al 16 demonstrated photomechanical manipulation of glycerol droplets in NLCs on the basis of photoisomerization of azo-benzene derivative. But the mixing of glycerol in ferroelectric LC ͑FLC͒, which are well known for their good optical contrast, low threshold voltage, memory effect, fast response, etc., is rather far from investigations.…”
Section: Introductionmentioning
confidence: 99%